Rancang Bangun Drone Flamethrower Alat Pembakar Layang-Layang Pada Saluran Transmisi Berbasis Arduino - Rindi Wulandari; Muhamad Riyad Ariwibowo; M. Angga Priyanto; Taryo (Universitas Islam Raden Rahmat, Malang, 2024)
Flying kites around transmission lines is prohibited. This is stated in the Minister of Energy and Mineral Resources' regulation Number 02 of 2019 concerning Free Space and Minimum Clearance on Electric Network Air Lines. To clean a kite using the conventional method requires the maintenance team to use a trash cleaning stick that is stuck in the conductor network or certain other methods. This tool is useful for burning kite waste that is stuck in transmission lines which is controlled using two controllers, namely transmitter and receiver with Arduino as the control center. This research uses quantitative methods of the Research and Development (R & D) type. The results obtained from this research show that based on test results, up to a distance of 20 meters this flamethrower drone can send and receive commands as desired and successfully burn kites on the electric power system network with a height of 17 meters and the average burning time for Burns 1 kite for 13 seconds. So it can be concluded that the design of the flamethrower drone can run well.